2005
DOI: 10.1007/s11121-005-3410-7
|View full text |Cite
|
Sign up to set email alerts
|

Schools and Homes in Partnership (SHIP): Long-Term Effects of a Preventive Intervention Focused on Social Behavior and Reading Skill in Early Elementary School

Abstract: This paper reports a randomized controlled trial of the effects of behavioral parenting skills training, social skills training, and supplemental reading instruction on the social behavior of early elementary school children (K through 3). We selected children based on teacher-rated aggressive behavior or reading-skill deficits, delivered the intervention over a 2-year period, and obtained follow-up data for two additional years. The intervention affected only two of eight measures of child functioning--parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
(36 reference statements)
1
21
0
Order By: Relevance
“…In particular, we expect that the early changes we see for 4Rs children in hostile attributional biases will translate into changes in aggressive and delinquent behavior in later elementary school, when these more serious behaviors begin to increase (e.g., Smolkowski et al, 2005). In addition, consistent with developmental cascades theory (Masten & Cicchetti, 2010), some of the unanticipated early effects we are observing in depressive symptoms might be expected to translate into universal benefits in other, related developmental domains later in elementary school (reduced academic disengagement/failure and delayed onset of substance use; e.g., Eddy, Reid, Stoolmiller, & Fetrow, 2003;Lochman & Wells, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we expect that the early changes we see for 4Rs children in hostile attributional biases will translate into changes in aggressive and delinquent behavior in later elementary school, when these more serious behaviors begin to increase (e.g., Smolkowski et al, 2005). In addition, consistent with developmental cascades theory (Masten & Cicchetti, 2010), some of the unanticipated early effects we are observing in depressive symptoms might be expected to translate into universal benefits in other, related developmental domains later in elementary school (reduced academic disengagement/failure and delayed onset of substance use; e.g., Eddy, Reid, Stoolmiller, & Fetrow, 2003;Lochman & Wells, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A possible association could be due to improved methodology in younger studies or minor modifications in the implementation of Triple P. The proportion of boys in the sample was of interest because there is evidence of differential relationships between dysfunctional parenting and child symptoms (Godkin and Schwenzfeier 1991) and parent training effectiveness for boys compared to girls (e.g., within the Incredible Years framework: Lavigne et al 2007;Smolkowski et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Following this definition, several conduct problems prevention programs have now reported that earlier gains in children's social, emotional,behavioral and academic functioning were maintained or strengthened during follow-up intervals (e.g., Peters & Petrunka, 2005;Reid et al, 2003). One program reported "sleeper effects," with improvements in children's antisocial behavior and parent ratings of coercive behaviors emerging anew during the follow-up period (Smolkowski et al, 2005). Other programs have shown that earlier gains translated into benefits in more distal outcomes such as reductions in delinquent behavior and substance use (e.g., Eddy et al, 2003;Lochman & Wells, 2004).…”
mentioning
confidence: 99%